Differentiation of Self and its Relationship with Marital Satisfaction and Parenting Styles in a Spanish Sample of Adolescents´ Parents - Mozas Alonso, Marta; Oliver-Pece, Jesús; Berástegui Pedro-Viejo, Ana (Public Library of Science (Plos One), 2022)
The present study aims to test some of the assumptions of Bowen’s Family Systems Theory, specifically, to assess the relationships between differentiation of self (DoS), marital satisfaction and parenting styles, as well as the gender differences in these variables in a Spanish sample. The sample includes 140 Spanish non-single adults, over 30 years old, who have at least one adolescent son or daughter, aged between 12 and 19 years old. The instruments used were a sociodemographic questionnaire, the Differentiation of Self Scale, the Warmth Scale-Parents, the Rules and Demands Scale-Parents and the Satisfaction subscale of the Dyadic Adjustment Scale. The results show DoS is related to marital satisfaction, and parenting styles’ dimensions. Regarding gender, women show higher emotional reactivity and warmth-communication than men do. Furthermore, marital satisfaction mediates the relationship between DoS and parental warmth-communication, criticism-rejection and inductive form. Finally, implications for clinical practice and future research are discussed.
Keywords: Familia; Matrimonio; Differentiation of self; Marital satisfaction; Parenting styles; Bowen’s Family Systems Theory